Technical Note - Development and extinguishment of oil shale rubble fire - M. J. Sapko; N. B. Greninger (Society for Mining, Metallurgy & Exploration, 1991)
The US Bureau of Mines conducted, through joint funding with the Colorado Mining Association, large scale oil shale rubble fire tests to investigate flammability characteristics and different methods of extinguishment. Ignition of large rubble piles was easily accomplished. Foam blankets could be used to control surface flames. The results of these large scale tests confirmed that water was effective but not particularly efficient in extinguishing deep seated oil shale fires. It took up to 1.7 times as much water to extinguish afire as anticipated on the basis of a simple cooling model, assuming 100% utiliza-